Minat, Perilaku Belajar Mahasiswa dan Tingkat Pemahaman Akuntansi Pengantar Berdasarkan Latar Belakang Pendidikan - Wulandari, Sri Ayu; Krisna Dewi, Luh Gede (E-Jurnal Akuntansi; Vol 31 No 1 (2021)DO - 10.24843/EJA.2021.v31.i01.p07, 2021)
The level of understanding of accounting principles is the foundation that greatly influences the choice of occupations of future employment. Some accounting graduates who have worked but not in their fields. This can be caused by lack of interest and poor learning behavior while undergoing education. This study aims to analyze the influence of students' interest and learning behavior on the level of understanding of accounting principles. This research was conducted at FEB Unud on S1 Accounting students in class 2018, with a purposive sampling method, totaling 200 respondents. Data collection through questionnaires. The data analysis technique used is multiple linear regression analysis. The results showed that interest and learning behavior had a positive and significant effect on the level of accountingprinciples understanding. The higher or better the interest and learning behavior, the higher the level of understanding of the accounting principles. Keywords: Interests; Behavior; Accounting Principles Understanding.